Donovanosis at "Dos de Mayo National Hopital", Lima-Peru 1991-1994 - Romero, Oscar (1995)
The donovanosis is a sexually transmitted disease wich is onlu diagnosed through biopsy and smears. Out of 2259 biopsies made by Dermatology Service from "Dos de Mayo National Hospital" in Lima-Peru since 1991 to 1994, 35 samples were positives to Leishman staining and HE. 83% (29) corresponded to make and 17% (6) to female, 60% patients ranged between 21 to 30 years old (10). This disease is localized in penis (34%)(12) and perianal (34%)(12) sites. It is important to underline the place of different injuries compared with those of other studies. A finding of injury in vulvus of puerpera is reported.